DDRE-24. ARF4-MEDIATED RETROGRADE TRAFFICKING PROMOTES CHEMORESISTANCE IN GBM. (12th November 2021) - Budhiraja, Shreya; Baisiwala, Shivani; Nandoliya, Khizar; Dara, Gabriel; Perrault, Ella; Zolp, Andrew; Chen, Li; Dmello, Crismita; Park, Cheol; Sonabend, Adam; Ahmed, Atique
Abstract: Glioblastoma (GBM) is the most common type of adult malignant brain tumor, with a median survival of only 21 months. This is partly due to the high rate of resistance to conventional therapy, including temozolomide (TMZ), leading to recurrence rates close to 100%. To identify the unknown genes driving the development of this resistance, we performed a genome-wide CRISPR knockout screen comparing a DMSO-treated population with a TMZ-treated population over 14 days. Results showed significant enrichment of ~200 novel genes and pathways. From this list, we identified 4 previously unstudied genes showing significant elevations in RNA expression ( p< 0.05 ) when comparing recurrent and primary tumors in patient datasets, along with significant survival benefits corresponding to low gene expression ( p< 0.05). Validation experiments in vitro showed significant elevations in RNA and protein expression in multiple patient-derived xenografts (PDX) lines during TMZ-treated conditions, while knocking out these genes also resulted in significantly heightened sensitivity to TMZ ( p< 0.01). We investigated one particularly enriched gene, ARF4, known to be involved in retrograde trafficking. With previous studies showing that ARF4 is upregulated under ER stress, we first confirmed the increased expression of ER stress markers during TMZ treatment to explain the increased expression of ARF4 during treatment. Further investigation via live-cell imaging also showed a consequent increase in retrograde trafficking in TMZ-treated cells, as evidenced by significantly increased trafficking of transferrin receptors, a retrograde transport marker, as well as EGFR, known to play a role in promoting chemoresistance through strengthened DNA repair response. ARF4-overexpressed GBM cells similarly showed increased trafficking of transferrin receptors and EGFR to the nucleus, while ARF4-knockdowns showed decreased trafficking and nuclear EGFR expression. Ultimately, our CRISPR-Cas9 screen has identified a promising therapeutic target, ARF4, which may drive GBM's robust resistance to chemotherapy through increased retrograde trafficking of chemoresistance-promoting nuclear EGFR.